TEACHING METHOD INVESTIGATION OF LI YANG’S CRAZY ENGLISH - Lusia Neti Harwati (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2022)
Calls for more holistic research, especially ones that deal with English teaching and learning have increased in recent years. Through critical literature review, this study examines Li Yang’s crazy English, as a trend of English teaching in China. More specifically, it aims to discuss whether Li Yang’s crazy English is one of the “designer” methods and will produce proficient English speakers by proposing two research questions: (1) what is the nature of the “designer” methods? and (2) what specific strategies and what approach to foreign language teaching have the potential to improve learners’ communicative competence in Li Yang’s teaching method? The data have been analyzed and it is found that Li Yang’s crazy English can be categorized as one of the “designers” methods, which is, Total Physical Response (TPR) and failed to build learners’ communicative competence as the ultimate goal of foreign language teaching. The study recommends, therefore, the use of communicative approach in English teaching and learning processes to produce proficient English speakers